A Duck is a Duck - Clymer, Theodore; Illustrated by Rebecca Gryspeerdt (Jordan Hill Ginn and Company, 2001)
The New Reading 360 series is designed to provide a solid literary foundation for infants and build on previous literacy knowledge for juniors. Readers help to develop literacy skills and build up confidence.
Include Illustration
Keywords: Reading (Primary)